Variance of genetic reducing sugars and dry matter and their correlations with agronomic traits in potatoes - Salamoni, Adriana Tourinho; Pereira, Arione da Silva; Viégas, Judith; Campos, Ângela Diniz; Chalá, Carla Simone de Almeida (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this research was to estimate the components of the variance and heritability relating to reducing sugars content and to dry matter, and their correlations with some agronomic traits of potato (Solanum tuberosum L.). Forty potato clones randomly chosen by the Embrapa-Centro de Pesquisa Agropecuária de Clima Temperado Breeding Program were used. The field experiments were carried out in the fall and in the spring of 1996, in Pelotas, RS, Brazil. Sugar and dry matter content were analyzed after storing tubers in cold chamber (5±1ºC). Genetic variances relating to reducing sugars and to dry matter content were moderate, and error variances were high, providing relatively low heritability values for both traits. The reducing sugar content was positively and significantly correlated with most of the agronomic traits and negatively correlated with dry matter content. The correlations between dry matter and agronomic traits were low and not significant.
Keywords: Solanum tuberosum; heritability; processing; quantitative genetics